Cp2TiCl-Mediated 5-exo-trig Radical Cyclization in Epoxy-Appended Olefin Diesters: Toward the Synthesis of Lingzhilactones - Khude, Kalpesh Ananda; Chakraborty, Tushar Kanti (Synlett, 2025)
The Cp2TiCl-mediated opening of epoxides in α,β-unsaturated ester-appended substrates leads to a cascading 5-exo-trig radical cyclization followed by lactonization yielding bicyclic lactone rings. Leveraging this strategic approach has become crucial in the construction of the core structure of many terpenoid natural products. In our present study, this methodology is further extended to the maleate/fumerate diester–appended substrates to give selectively only the 5-exo ring closure products with the [5,5] bicyclic lactone framework. This arranged the basis of a facile approach to attempt the synthesis of lingzhilactone B, an important Ganoderma meroterpenoid with two all-carbon quaternary chiral centers in the ring junction, from easily available starting materials. The modular strategy developed here can pave the synthetic pathways for many other natural products of this genre.
Keywords: HWE olefination; Nozaki–Hiyama–Kishi coupling; Ti(III)-mediated Radical cyclization; Sharpless Epoxidation; Lingzhilactones